Traumatic Femoral Arteriovenous Fistula Mimicking Chronic Venous Insufficiency with Concurrent Iliac and Femoral Artery Aneurysms: A Case Report - Tommy Kuswara; Ramzi Azrial; Tania Nugrah Utami (HM Publisher, 2025)
Background: Traumatic arteriovenous fistulas (AVFs), constituting approximately 2.5% of emergency vascular cases, present diagnostic challenges due to their obscure nature. This report describes two cases of traumatic AVFs caused by gunshot wounds. Case presentation: A 61-year-old male presented with right lower extremity pain and swelling, following a gunshot wound four months prior. Clinical findings included discoloration, edema, vein swelling, and pain from the femoral to pedis regions. CT angiography revealed multiple aneurysms from the lower abdominal aorta to the right common iliac arteries, stenosis in the right external iliac artery, and reduced blood perfusion. Additional findings were tubular aneurysms in the external and internal right iliac arteries and a combination saccular-tubular aneurysm in the right femoral artery. A second, separate case also involved a traumatic AVF from a gunshot wound. Conclusion: Traumatic AVFs, particularly those resulting from gunshot wounds, can be difficult to diagnose early due to their rarity and obscure presentation. Early diagnosis is crucial to prevent disease progression and improve clinical outcomes. Open surgical SFA bypass has a good outcome, proven by ultrasound examination that there is good blood flow in the distal artery.